2020
DOI: 10.2147/dmso.s254586
|View full text |Cite
|
Sign up to set email alerts
|

<p>Limb Salvage and Prevention of Ulcer Recurrence in a Chronic Refractory Diabetic Foot Osteomyelitis</p>

Abstract: Biomechanical changes caused by structural foot deformities predispose patients to plantar ulceration. Plantar ulcer recurrence often leads to osteomyelitis, which is more commonly observed in patients with diabetes. Once the infection of diabetic foot ulcer (DFU) spreads and is complicated by osteomyelitis, treatment becomes more complicated and difficult. Osteomyelitis treatment remains challenging because of low drug concentration within the tissue caused by poor circulation and inadequate localized nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“… 14 This system is equipped with a triaxial accelerometer and gyroscope that estimates temporal gait, balance, and spatial parameters described in our previous study. 8 It generates digitized signals at a frequency of 100 Hz, which is transmitted in real-time via Bluetooth to a laptop. The participants were assessed on multiple static, dynamic parameters of gait and balance.…”
Section: Methodsmentioning
confidence: 99%
“… 14 This system is equipped with a triaxial accelerometer and gyroscope that estimates temporal gait, balance, and spatial parameters described in our previous study. 8 It generates digitized signals at a frequency of 100 Hz, which is transmitted in real-time via Bluetooth to a laptop. The participants were assessed on multiple static, dynamic parameters of gait and balance.…”
Section: Methodsmentioning
confidence: 99%
“…PRP has been widely used in the field of repair and regeneration, including in chronic tendinitis 2 , osteoarthritis 3 , chronic wounds 4 , and plastic surgeries 5 . A series of our previous studies on PRP treatment has revealed positive effects on wound healing in patients with diabetic foot ulcers 6 – 9 . The basic cytokines identified in platelets include transforming growth factor-ÎČ (TGF-ÎČ), platelet-derived growth factor (PDGF), basic fibroblast growth factor (bFGF), vascular endothelial growth factor (VEGF), and endothelial cell growth factor.…”
Section: Introductionmentioning
confidence: 99%
“…Results from our previous study, in which we explored use of offloading device in neuropathic diabetic foot, revealed that the device changed plantar biomechanics using wearable sensor technology. 8,25 Notably, this offloading therapy significantly improved clinical outcomes in these patients although one case who underwent IOT presented with recurrence during interruption of the therapy. 8 In the current study, we further explored the effects of interrupting offloading therapy on recurrence and mortality rates in high-risk diabetic foot patients.…”
Section: Discussionmentioning
confidence: 92%